Impact of heat reflective coatings on heat flows through the ventilated roof with steel coatings - Banionis, Karolis; Monstvilas, Edmundas; Stankevičius, Vytautas; Bliudžius, Raimondas; Miškinis, Kęstutis (Journal of Civil Engineering and Management, 2012)
In many EU countries, the normative requirements for thermal characteristics of roofs are associated only with rating the heat losses through the roofs during the heating period. The problem of overheated premises under the light-weight ventilated roofs, covered with steel sheets, arises in the summer time. During this period of the year, because of the intensive solar radiation and high air temperature, the steel roof coatings heat up during the day and cause additional heat inflows to the premises. One of the most effective means to reduce the additional radiative heat flow from the interior surfaces of the roof coating into the attic is to install radiant barriers with low emissivity coefficient into the roof construction. The experimental research has shown that having heat reflective coatings with low emissivity coefficient (ε = 0.09) installed on the exterior surface of the thermal insulation layer of the ventilated roofs with steel coatings, the heat flow from the roof coating through the roof construction into the interior premises can be reduced on the daily average of 23–25% in the summer time.